THE INFLUENCE OF CAREER DEVELOPMENT AND COMPETENCE ON EMPLOYEE SATISFACTION THROUGH WORK MOTIVATION AS INTERVENING VARIABLE AT PT. NIPPON SHOKUBAI INDONESIA CILEGON - Mela Sandra (Amal Insani Foundation, 2021)
ABSTRACT This study aims todetermine whether or not the effect of career development and competence on employee satisfaction through work motivation as an intervening variable. The study design used is descriptive and causal designs is to analyze the relationships between one variable with another variable using statistic. Methods of data collection in this study is a questionnaire or aquestionnaire. The sampling techniqueusedis the technique ofrandom sampling. The population of the research objectis PT.Nippon Shokubai Indonesia Cilegon with a sample of 82 employees. Hypothesis testingis done by linear regression analysis and path analysis (path analyze) by SPSS 20.0for windows. Based on the research results with significance level of 5% was obtained conclusions: (1) significantly influence the Career Development Job Satisfaction with correlation coefficient 0.018 and the t (2.418)> t table (1.990), then H0 rejected and H1 accepted; (2) there is no significant effect on Job Satisfaction Competency with r value of 0.392 and the t (0.115) <t table (1.990), then H0 is accepted and rejected H2; (3) there is a significant influence on the motivation of Career Development Working with r values ​​of 0.00 and the t (5.606)> t table (1.990), then H0 and H3 is accepted; (4) there is influence is insignificant Competence to Work Motivation Employees with r value of 0.473 and the t (0.721 <t table (1.997), then H0 is accepted and H4 is rejected; (5) there is significant influence work motivation Work on Employee Satisfaction the r value of 0.00 and the t (5.893> t table (1.997), then H0 and H5 accepted. Keywords: Career Development, Competence, Employee Satisfaction, and Work Motivation